PERCEPTION ON THE COMMITMENT OF ORGANIZATION BOARD: MODELING WITH IMPORTANCE PERFORMANCE ANALYSIS (Talenta Publisher, 2018)
This paper aims to find out the perception of an organization member on the commitment of its management. The variables studied are the level of importance and the level of satisfaction of the management performance. The sample used is taken proportionally from an organizational environment. Data collection methods using questionnaires and conducting interviews directly with respondents. The method used to measure perceptions using the Importance Performance Analysis (IPA) method. Statements are based on five characteristic dimensions according to the SERVQUAL method. in the paper using SPSS 22.00 syntax to measure the validity, reliability and analysis of research data. The results of data analysis will be able to explain the very dominant factors that affect the interests and satisfaction of organizational members on the performance of the board, so that it can contribute to the improvement of the vision and mission of the organization.